Effects of platelet‐rich fibrin on human gingival and periodontal ligament fibroblast proliferation from chronic periodontitis versus periodontally healthy subjects. Issue 4 (14th January 2021) - Goel, Apoorv; Windsor, L. Jack; Gregory, Richard L.; Blanchard, Steven B.; Hamada, Yusuke
Abstract: Background: Platelet‐rich fibrin (PRF), an autogenous blood concentrate, contains multiple growth factors and is used as an adjunct in the periodontal regeneration and implant site development procedures to stimulate wound healing. Patient‐related factors such as chronic periodontitis may affect the quality of PRF. Objectives: This study aimed to investigate and compare PRF's effects from patients diagnosed with generalized moderate or severe chronic periodontitis to patients who presented with intact periodontium on human gingival fibroblast (HGF) and human periodontal ligament fibroblast (HPLF) proliferation. Materials and methods: A total of 33 ml of whole intravenous blood was collected from each subject and centrifuged at 2700 rpm for 12 min in three 10 ml tubes, and 3 ml of blood was used for Complete Blood Count analysis. Three PRF clots were compressed to produce the membranes and liquid exudate. PRF membrane and 10% liquid exudate were exposed to 20, 000 HPLFs/well or 25, 000 HGFs/well in triplets from each subject in a 48 cell well plate. After 72 h of incubation, the conditioned media were evaluated by Water Soluble Tetrazolium‐1 assays to determine fibroblast proliferation. Controls included cells alone and media without cells. Complete blood counts were measured. Results: Subjects in both groups were age and gender‐matched (intact 46.7 ± 11.4 years and periodontitis 54.8 ± 10.4 years, p ‐value = 0.1344). Body Mass Index and White Blood Corpuscles in the periodontitis group was significantly higher than the intact group ( p  = 0.0176 and p  = 0.0038) whereas no differences were seen for Red Blood Corpuscles ( p  = 0.2020), Hemoglobin ( p  = 0.2290) and Platelets ( p  = 4, 094). There were no significant differences in the HGF and HPLF proliferation with PRF exudates and membranes between intact periodontium and periodontitis groups (all p  > 0.05). However, PRF exudates in both groups induced significant more cell proliferation when compared to PRF membranes. Conclusions: PRF exudates induced significant proliferation of fibroblasts and can play a vital role in wound healing. The current study concluded that PRF membranes, in combination with PRF exudates, can be utilized for their therapeutic and wound healing potential, not affected by the periodontal condition of the patient.